MEASUREMENT AND EVALUATION IN THE NOBLE QURAN (SURAT AN-NAML AS A MODEL) - Munadhil Adil Kasim; Emad Kadhim Katea; Haidar Hussein Odeh (Scholars Digest Publishing, 2025)
This research addressed the topic of appraisal and measuring in the Holy Quran. The objective was to find the terminology within the Holy Qur'an pertaining to assessment and measurement, and to ascertain the standards governing the processes of evaluation and measurement, whether concerning instruments, evaluators, or those responsible for them.
Keywords: Measurement, Calendar, Holy Quran, Surat An-Naml.